DESAIN PENGEMBANGAN KURIKULUM INTEGRATIF DAN IMPLEMENTASINYA DALAM PEMBELAJARAN - Mukhlasin, Ahmad; Wibowo, Rachmat (IAIIG Cilacap, 2018)
The curriculum as a system as well as a tool to achieve the goal of education becomes very urgent and absolute in an educational program. The curriculum is not enough just to contain the competences of students only, but the curriculum must also be able to synergize with all aspects of human life. This is the importance of the integrative curriculum as an integrated learning system both between its contents and the reality of human needs. On the one hand, a system will work best if the system is well planned, organized and applied properly. This means that the design of a curriculum will also determine whether the curriculum will be accomplished and deliver on the educational objectives or be forced to fail and need to be redesigned.The design of integrative curriculum development is the effort to develop the curriculum to develop the ability of reasoning in the formation of knowledge based on interaction with the environment and experience in life. This approach is intended as an effort to integrate three things namely the development, growth and ability of learners' knowledge.Keywords: design, integrative curriculum, and implementation